Development of a low cost smart traffic controller system - Purnomo, Muhammad Ridwan Andi; Wahab, Dzuraidah; Hassan, Azmi; Rahmat, Riza Atiq (EuroJournals Publishing, Inc., 2009)
This paper presents the development of a low cost smart traffic controller system. The proposed smart traffic controller system consists of two parts, which are the controller hardware and the software. The controller hardware is developed based on 8-kb MCS-51 microcontroller and equipped with a character LCD to monitor the internal timer, Real Time Clock (RTC) IC to generate time and date data and EEPROM IC to save the green time data at several time periods. The software is developed to enable the controller hardware interfacing with the CCTV cameras as the traffic sensors, when used to optimise the traffic flow at some junction. The software also can be used by the traffic expert to change the setting of the controller hardware and perform manually control the traffic lights through the controller hardware. Another function of the software is to perform traffic data interchange. It will enable the controller hardware to communicate with other controllers that are installed at the nearby junctions in order to optimise the traffic flow at the network junction. The proposed smart traffic controller system is able to realise three kinds of traffic flow optimisation strategies, which are green time split and time slot timing, green time extension or vehicle actuated green time and offset optimisation strategy. The proposed smart traffic controller system has been tested by installing at several busy junctions in Malaysia for more than a year, and it shows that the proposed smart traffic controller system performs better than the existing traffic controller system. When the traffic flow optimisation strategies are applied and realised using the proposed smart traffic controller system, the total vehicles queuing time is reduced by up to 30% compared to when using the existing traffic controller system.